Comparative Proteomics of Outer Membrane Vesicles from Polymyxin-Susceptible and Extremely Drug-Resistant Klebsiella pneumoniae - Maytham Hussein; Raad Jasim; Hakan Gocol; Mark Baker; Varsha J. Thombare; James Ziogas; Aayush Purohit; Gauri G. Rao; Jian Li; Tony Velkov (mSphere, 2023)
ABSTRACT Outer membrane vesicles (OMVs) secreted by Gram-negative bacteria serve as transporters for the delivery of cargo such as virulence and antibiotic resistance factors. OMVs play a key role in the defense against membrane-targeting antibiotics such as the polymyxin B. Herein, we conducted comparative proteomics of OMVs from paired Klebsiella pneumoniae ATCC 700721 polymyxin-susceptible (polymyxin B MIC = 0.5 mg/L) and an extremely resistant (polymyxin B MIC ≥128 mg/L), following exposure to 2 mg/L of polymyxin B. Comparative profiling of the OMV subproteome of each strain revealed proteins from multiple perturbed pathways, particularly in the polymyxin-susceptible strain, including outer membrane assembly (lipopolysaccharide, O-antigen, and peptidoglycan biosynthesis), cationic antimicrobial peptide resistance, β-lactam resistance, and quorum sensing. In the polymyxin-susceptible strain, polymyxin B treatment reduced the expression of OMV proteins in the pathways related to adhesion, virulence, and the cell envelope stress responses, whereas, in the polymyxin-resistant strain, the proteins involved in LPS biosynthesis, RNA degradation, and nucleotide excision repair were significantly overexpressed in response to polymyxin B treatment. Intriguingly, the key polymyxin resistance enzymes 4-amino-4-deoxy-l-arabinose transferase and the PhoPQ two-component protein kinase were significantly downregulated in the OMVs of the polymyxin-susceptible strain. Additionally, a significant reduction in class A β-lactamase proteins was observed following polymyxin B treatment in the OMVs of both strains, particularly the OMVs of the polymyxin-susceptible strain. These findings shed new light on the OMV subproteome of extremely polymyxin resistant K. pneumoniae, which putatively may serve as active decoys to make the outer membrane more impervious to polymyxin attack. IMPORTANCE OMVs can help bacteria to fight antibiotics not only by spreading antibiotic resistance genes but also by acting as protective armor against antibiotics. By employing proteomics, we found that OMVs have a potential role in shielding K. pneumoniae and acting as decoys to polymyxin attack, through declining the export of proteins (e.g., 4-amino-4-deoxy-l-arabinose transferase) involved in polymyxin resistance. Furthermore, polymyxin B treatment of both strains leads to shedding of the OMVs with perturbed proteins involved in outer membrane remodeling (e.g., LPS biosynthesis) as well as pathogenic potential of K. pneumoniae (e.g., quorum sensing). The problematic extended spectrum beta-lactamases SHV and TEM were significantly reduced in both strains, suggesting that polymyxin B may act as a potentiator to sensitize the bacterium to β-lactam antibiotics. This study highlights the importance of OMVs as “molecular mules” for the intercellular transmission and delivery of resistance and cellular repair factors in the bacterial response to polymyxins.